2017
DOI: 10.1016/j.sjbs.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of quercetin in diabetic rat retina

Abstract: Diabetic retinopathy (DR) is a severe complication of diabetes and the leading cause of blindness among working adults worldwide. DR is being widely recognized as a neurodegenerative disease of the retina, since, retinal neurons are damaged soon after diabetes onset. Diabetes-induced oxidative stress is considered as central factor that dysregulates neurotrophic factors and activates apoptosis, thereby damages neurons in the diabetic retina. Flavonoids being a powerful antioxidant have been considered to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Similarly, some other studies have demonstrated obvious neurodegenerative histological changes of retinal tissue in the early stages of diabetes, and the underlying neuroprotective impacts of natural phenolic compounds have been reported to be correlated with activation of PI3 K/AKT signaling pathway …”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Similarly, some other studies have demonstrated obvious neurodegenerative histological changes of retinal tissue in the early stages of diabetes, and the underlying neuroprotective impacts of natural phenolic compounds have been reported to be correlated with activation of PI3 K/AKT signaling pathway …”
Section: Resultsmentioning
confidence: 63%
“…Overall, the reduction of AKT activation has an important role in the retinal neurodegeneration . Treatment with natural polyphenolic compounds has been shown to exert a significant neuroprotection possibly through enhancement of p‐AKT levels in animal model of diabetic retinopathy, and neuropathy …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Qcn preserved the visual function, prevented apoptosis of RGC, decreased the macrophage/microglial infiltration in the ONs, and impeded the secondary RGC death. Qcn was administered by intraperitoneal, oral, or intravitreal injection on the retina as described previously [17,22,23]. However, based on the pharmacodynamic maintenance and prolonged exposure of Qcn on the retina, we selected the intravitreal injection as the mode of Qcn administration.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structural formulas of QU, KA, GI and SC are shown in Figure 1. These four flavonoids have many pharmacological activities, including anti-inflammatory, anti-tumor, anti-influenza virus, anti-platelet aggregation, cardiovascular protection and blood glucose regulation, improving depression associated with epilepsy and immunosuppressive activity [13][14][15][16][17][18][19][20][21][22]. The traditional method for extraction of flavonoids is mainly heating reflux extraction (HRE).…”
Section: Introductionmentioning
confidence: 99%